1997
DOI: 10.1177/000348949710600909
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sinus Irrigation versus Sinus Irrigation Followed by Functional Endoscopic Sinus Surgery

Abstract: Sinus irrigation is the traditional treatment for chronic maxillary sinusitis. Functional endoscopic sinus surgery (FESS) restores aeration and allows secretions to be removed from an infected sinus. This study compares the efficacy of sinus irrigation with that of sinus irrigation followed by FESS in 89 patients. We measured the effects by way of sinus radiographs, nasendoscopic findings, and patient complaints. When we analyzed the data in terms of intent to treat, we found significantly favorable results fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…A Cochrane Review in 2006 1130 based on 3 RCTs suggested that ESS did not offer additional benefit when compared to medical therapies. 751,1344 However, the included trials evaluated patients who had not failed a trial of appropriate medical therapy prior to randomization. Smith et al 1131,1148,1342 published subsequent nonrandomized, real-world, multicenter observational studies and have demonstrated significant benefits of ESS over continued medical therapy in patients who have failed an initial trial of appropriate therapy.…”
Section: Xf Surgery For Crswnp and Crssnp: Outcomesmentioning
confidence: 99%
“…A Cochrane Review in 2006 1130 based on 3 RCTs suggested that ESS did not offer additional benefit when compared to medical therapies. 751,1344 However, the included trials evaluated patients who had not failed a trial of appropriate medical therapy prior to randomization. Smith et al 1131,1148,1342 published subsequent nonrandomized, real-world, multicenter observational studies and have demonstrated significant benefits of ESS over continued medical therapy in patients who have failed an initial trial of appropriate therapy.…”
Section: Xf Surgery For Crswnp and Crssnp: Outcomesmentioning
confidence: 99%
“…However, the tenants of a RDBPCT are not easily applied to surgical outcomes as obvious problems with randomization, blinding, and sham surgeries arise. To our knowledge, only two randomized studies have compared medical regimens to ESS for adult patients with CRS35,36. Both of these were done outside of the United States and showed no difference in outcomes when comparing ESS to medical treatments of CRS.…”
Section: Important Weaknesses Exist In Current Qol Outcomes Studiesmentioning
confidence: 99%
“…Neither showed statistically significant differences. However, none of them followed the patients after the cessation of drug therapy 22,23 . Many studies done in the past to assess the effectiveness of FESS in the treatment of chronic rhinosinusitis patients used non-validated QoL questionnaires and looked into the presence or absence of certain symptoms, alterations viewed endoscopically or on CT scans [24][25][26] .…”
Section: Fortymentioning
confidence: 99%